Influence of molecular structure on the antimicrobial function of phenylenevinylene conjugated oligoelectrolytes. Issue 9 (14th June 2016) - Yan, Hengjing; Rengert, Zachary D.; Thomas, Alexander W.; Rehermann, Carolin; Hinks, Jamie; Bazan, Guillermo C.
Abstract : Structure/property relationships were obtained to understand the antimicrobial function of conjugated oligoelectrolytes toward Gram-negative and Gram-positive bacteria. Abstract : Conjugated oligoelectrolytes (COEs) with phenylenevinylene (PV) repeat units are known to spontaneously intercalate into cell membranes. Twelve COEs, including seven structures reported here for the first time, were investigated for the relationship between their membrane disrupting properties and structural modifications, including the length of the PV backbone and the presence of either a tetraalkylammonium or a pyridinium ionic pendant group. Optical characteristics and interactions with cell membranes were determined using UV-Vis absorption and photoluminescence spectroscopies, and confocal microscopy. Toxicity tests on representative Gram-positive ( Enterococcus faecalis ) and Gram-negative ( Escherichia coli ) bacteria reveal generally greater toxicity to E. faecalis than to E. coli and indicate that shorter molecules have superior antimicrobial activity. Increased antimicrobial potency was observed in three-ring COEs appended with pyridinium ionic groups but not with COEs with four or five PV repeat units. Studies with mutants having cell envelope modifications indicate a possible charge based interaction with pyridinium-appended compounds. Fluorine substitutions on COE backbones result in structures that are less toxic to E. coli, while the addition of benzothiadiazole to COE backbones has no effect on increasing antimicrobial function. A weakly membrane-intercalating COE with only two PV repeat units allowed us to determine the synthetic limitations as a result of competition between solubility in aqueous media and association with cell membranes. We describe, for the first time, the most membrane disrupting structure achievable within two homologous series of COEs and that around a critical three-ring backbone length, structural modifications have the most effect on antimicrobial activity.